2015
DOI: 10.1158/1535-7163.mct-14-0481
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 6 Represents a Novel Drug Target in the Oncogenic Hedgehog Signaling Pathway

Abstract: Uncontrolled Hedgehog (Hh) signaling is the cause of several malignancies, including the pediatric cancer medulloblastoma, a neuroectodermal tumor affecting the cerebellum. Despite the development of potent Hh pathway antagonists, medulloblastoma drug resistance is still an unresolved issue that requires the identification of novel drug targets. Following up on our observation that histone deacetylase 6 (HDAC6) expression was increased in Hh-driven medulloblastoma, we found that this enzyme is essential for fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 80 publications
1
37
0
Order By: Relevance
“…In a previous report it was observed that, in addition to HDAC1/2, HDAC6 is also upregulated in SHH-MB and its targeting leads to a substantial anti-tumor effect in mouse models of SHH-MB29. Interestingly, HDAC6 seems to exert its function independently of Gli acetylation, by acting at both receptor and downstream level, most likely by affecting Gli2/3 stability.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous report it was observed that, in addition to HDAC1/2, HDAC6 is also upregulated in SHH-MB and its targeting leads to a substantial anti-tumor effect in mouse models of SHH-MB29. Interestingly, HDAC6 seems to exert its function independently of Gli acetylation, by acting at both receptor and downstream level, most likely by affecting Gli2/3 stability.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, HDAC1/2 deacetylate and enhance Gli1 transcriptional activity, thus suggesting that, by blocking these enzymes, MGCD0103 may inhibit Hh function via Gli1 acetylation. Since in a recent work it was also observed that HDAC6 inhibits Hh signaling by acting both upstream and downstream of Sufu29, we first tested at what level the inhibitory effect of MGCD0103 occurs. To this end, we used the Sufu −/− MEF cells, where the absence of the cytoplasmic inhibitor Sufu causes an increase of Hh target gene expression, independently of the receptor (Ptch1/Smo) activation30.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that selective inhibition of HDAC6 can represents a new therapeutic approach in the treatment of Hh-dependent malignancies. Indeed, the specific HDAC6 antagonist, ACY-1215 [70] ( Figures 1 and 2 and Table 1), reduced strikingly in vivo tumor growth. Hence, HDAC6, despite exerting a dichotomous role (it is required to achieve full pathway activity, but it has also been described to repress basal Hh target gene transcription) is a critical player in Hh pathway regulation, promoting the maximum expression of a subset of GLI target genes [70].…”
Section: Hdac Inhibitors (Hdacis)mentioning
confidence: 98%
“…Indeed, the specific HDAC6 antagonist, ACY-1215 [70] ( Figures 1 and 2 and Table 1), reduced strikingly in vivo tumor growth. Hence, HDAC6, despite exerting a dichotomous role (it is required to achieve full pathway activity, but it has also been described to repress basal Hh target gene transcription) is a critical player in Hh pathway regulation, promoting the maximum expression of a subset of GLI target genes [70]. Since the upregulation of HDACs has been documented in various types of tumors, the development of novel potent and selective HDACi is ongoing.…”
Section: Hdac Inhibitors (Hdacis)mentioning
confidence: 98%
“…A similar induction of GLI1 was observed in MEFs treated with the pan-HDACi trichostatin A. 34 The canonical role of GLI1 is as a key transcription factor and effector molecule in the Hedgehog signaling pathway. 25 As SMO inhibition did not sensitize to vorinostat-induced apoptosis, GLI1 appears to function through a noncanonical pathway in this system.…”
Section: Discussionmentioning
confidence: 60%